Compensatory contribution of retinal larger vessels to perfusion density in diabetics without retinopathy - Blanco-Hernández, Dulce Milagros Razo; Somilleda-Ventura, Selma Alin; Chávez-Herrera, Rebeca; Colas-Calvere, María Guadalupe; Lima-Gómez, Virgilio (Scientific reports, 2022)
Vessel and perfusion densities may decrease before diabetic retinopathy appears; it is unknown whether these changes affect the contribution of vessel density to perfusion density. This was a non-experimental, comparative, prospective, cross-sectional study in non-diabetic subjects (group 1) and diabetics without retinopathy (group 2). Vessel and perfusion densities in the superficial capillary plexus were compared between groups at the center, inner, and full regions and by field (superior, temporal, inferior, nasal) using optical coherence tomography angiography. Coefficients of determination (R 2 ) between vessel and perfusion densities were calculated to find the contribution of larger retinal vessels to perfusion density. Percent differences were used to evaluate the contribution of these vessels to perfusion density in a regression model. There were 62 participants, 31 eyes by group; vessel and perfusion densities as well as the coefficients of determination between them were lower in group 2, especially in the nasal field (R 2 0.85 vs. 0.71), which showed a higher contribution of larger retinal vessels to perfusion density. The regression model adjusted to a quadratic equation. In diabetics without retinopathy the contribution of vessel density to perfusion density may decrease; a low vessel density may increase the contribution of larger retinal vessels to perfusion density.